EFFECT OF TILLAGE, CROP ROTATION AND PREVIOUS CROP RESIDUES ON CLOVER, MAIZE AND MUNG BEAN PRODUCTIVITY - H. T. R. Al-Furaiji,; N. S. Ali, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Two field experiments were conducted to evaluate the effect of tillage, crop residues and crop rotation on productivity of clover, maize and mung bean, at the experimental research station of the College of Agricultural Engineering Sciences - University of Baghdad in Aljadriya, Baghdad – Iraq during two seasons of 2021-2022. 1st trail was with two factors: residues (0%R and 100%R) and tillage (minimum (MT) and conventional (CT)) with four replicates. Results indicated the best values of height and dry matter yield were (70.25 cm and 5.558 Mg ha-1) for (100%R+MT) compared with (65.5 cm and 4.985 Mg ha-1) for (0%R+CT) respectively. The 2nd trail was with three factors: the same tillage and residues coupled with crop rotations (clover-maize) and (clover-mung bean). Results (representing the accumulated effect of both trials) indicated the best values of height, dry matter yield and grains and seeds  yield were (236.25 and 111.5) cm, (4.560 and 14.745) Mg ha-1, (6.840 and 3.754) Mg ha-1 for (100%R+MT) treatment compared to (210.0 and 101.25) cm, (4.048 and 11.337) Mg ha-1, (5.685 and 2.829) Mg ha-1 with (0%R+CT) for maize and mung bean respectively and under crop rotations (clover-maize) for maize and (clover- mung bean) for mung bean.